Feasibility of progressive sit-to-stand training among older hospitalized patients - Pedersen,Mette Merete; Petersen,Janne; Bean,Jonathan F.; Damkjaer,Lars; Juul-Larsen,Helle Gybel; Andersen,Ove; Beyer,Nina; Bandholm,Thomas (PeerJ, 2015)
Background. In older patients, hospitalization is associated with a decline in functional performance and loss of muscle strength. Loss of muscle strength and functional performance can be prevented by systematic strength training, but details are lacking regarding the optimal exercise program and dose for older patients. Therefore, our aim was to test the feasibility of a progression model for loaded sit-to-stand training among older hospitalized patients. Methods. This is a prospective cohort study conducted as a feasibility study prior to a full-scale trial. We included twenty-four older patients (≥65 yrs) acutely admitted from their own home to the medical services of the hospital. We developed an 8-level progression model for loaded sit-to-stands, which we named STAND. We used STAND as a model to describe how to perform the sit-to-stand exercise as a strength training exercise aimed at reaching a relative load of 8–12 repetitions maximum (RM) for 8–12 repetitions. Weight could be added by the use of a weight vest when needed. The ability of the patients to reach the intended relative load (8–12 RM), while performing sit-to-stands following the STAND model, was tested once during hospitalization and once following discharge in their own homes. A structured interview including assessment of possible modifiers (cognitive status by the Short Orientation Memory test and mobility by the De Morton Mobility Index) was administered both on admission to the hospital and in the home setting. The STAND model was considered feasible if: (1) 75% of the assessed patients could perform the exercise at a given level of the model reaching 8–12 repetitions at a relative load of 8–12 RM for one set of exercise in the hospital and two sets of exercise at home; (2) no ceiling or floor effect was seen; (3) no indication of adverse events were observed. The outcomes assessed were: level of STAND attained, the number of sets performed, perceived exertion (the Borg scale), and pain (the Verbal Ranking Scale). Results. Twenty-four patients consented to participate. Twenty-three of the patients were tested in the hospital and 19 patients were also tested in their home. All three criteria for feasibility were met: (1) in the hospital, 83% could perform the exercise at a given level of STAND, reaching 8–12 repetitions at 8–12 RM for one set, and 79% could do so for two sets in the home setting; (2) for all assessed patients, a possibility of progression or regression was possible—no ceiling or floor effect was observed; (3) no indication of adverse events (pain) was observed. Also, those that scored higher on the De Morton Mobility Index performed the exercise at higher levels of STAND, whereas performance was independent of cognitive status. Conclusions. We found a simple progression model for loaded sit-to-stands (STAND) feasible in acutely admitted older medical patients (≥65 yrs), based on our pre-specified criteria for feasibility.
Keywords: Older medical patients; Strength training; Cross continuum; Supervision; Physical therapy